Monthly girls' Nozaki-kun. 1 - Tsubaki, Izumi (Yen Press/Hachette Book Group, 2015)
"To the eyes of classmate Chiyo Sakura, high school student Umetarou Nozaki--brawny of build and brusque of tongue--is a dreamboat! When Chiyo finally works up the courage to tell Nozaki how she feels about him, she knows rejection is on the table...but getting recruited as a mangaka's assistant?! Never in a million years! As Chiyo quickly discovers, Nozaki-kun, the boy of Chiyo's dreams, is a manga artist...a hugely popular shoujo manga artist, that is! But for someone who makes a living drawing sweet girly romances, Nozaki-kun is a little slow on the uptake when it comes to matters of the heart in reality. And so Chiyo's daily life of manga making and heartache begins!"--Page 4 of cover.